A Qualitative Research for Determining the Approaches for the Separation of Turkey into Geographical Regions - (:unkn) unknown (MARMARA UNIV, 2018)
This study aims to evaluate the approaches of geographers, geography teachers and geography teacher candidates regarding the distinction of Turkey into geographic regions. For this purpose, 15 questions were identified related to the geographic regions. A pretest for the content validity of the questions was conducted with experts. Completely allied questions by experts have been used for collecting data in the prepared form. Questionnaires consisting of open-ended questions which was applied according to the purposive sampling strategy. The obtained data from questionnaire were processed by descriptive analysis. The findings, discussions and suggestions of the study concluded about criteria for the distinction of existing geographical regions, advantages and disadvantages of the distinction, necessary or unnecessary of geographic regions, views on how this should be done, causes of region and province boundaries do not overlap with each other, the opinions expressed in the news bulletins of the weather condition according to the regions, why region boundaries can be drawn or cannot be drawn with ruler, to remove the region borders or not, and how can we use different criteria for new geographic regions according to needs.
Keywords: Geographic Region; Physical Region; Human Region; Sense of Region; Region Border